Hot House Global Climate Change and the Human Condition - Strom, Robert; SpringerLink (Online service) (New York, NY : Springer New York, 2007)
Global warming is extremely complex because it deals with so many different characteristics of the Earth and their complex interactions. It is addressed by almost all sciences including many aspects of geosciences, atmospheric, the biological sciences, and even astronomy. It has recently become the concern of other diverse disciplines such as economics, agriculture, demographics and population statistics, medicine, engineering, and political science. This book attempts to address these complex interactions, integrate them, and derive meaningful conclusions and possible solutions. Robert Strom provides a complete, easy-to-read explanation of past and present global climate change, causes and possible solutions to the problem, including the politics and reasons why this is such a politically charged issue.
A Gigantic Experiment -- The ABCs of Climate Change -- A Planetary Perspective -- Time and Causes -- A Hot and Cold Past -- The Heat Is On -- The Human Impact -- The Main Offenders -- The Root Cause -- The Melting Earth -- Water World -- What$1 (Bs in Store for Us? -- The Escape Hatch -- Politics and Money -- It$1 (Bs Now or Never.s
Keywords: Popular works; Climate change; Planetology; Nature; Environment; Popular Science; Popular Science in Nature and Environment; Climate Change Management and Policy; Planetology; Electronic books